2009
DOI: 10.2319/091907-450.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Created Nonbalanced Occlusion Effects on the Thickness of the Temporomandibular Joint Disc in Rats

Abstract: Objectives:To test the hypothesis that experimentally created physiologically nonbalanced occlusion will not affect the thickness of the temporomandibular joint (TMJ) discs in rats. Material and Methods: Twenty-four 8-week-old Sprague-Dawley rats were equally divided into a control group that was left untreated and an experimental group where a nonbalanced occlusion was created. Elastic rubber bands, 1 mm in diameter, were inserted and 1 week later were replaced by plastic material between the first and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
11
2
Order By: Relevance
“…For rats in the experimental group, the first left maxillary and the first right mandibular molars were moved medially as previously described [27]. Briefly, an elastic rubber band (3 M Unitek, 1/8#), about 1 mm in diameter, was inserted between the first and second left maxillary molars and between the first and second right mandibular molars.…”
Section: Experimentally Created Disordered Occlusionmentioning
confidence: 99%
“…For rats in the experimental group, the first left maxillary and the first right mandibular molars were moved medially as previously described [27]. Briefly, an elastic rubber band (3 M Unitek, 1/8#), about 1 mm in diameter, was inserted between the first and second left maxillary molars and between the first and second right mandibular molars.…”
Section: Experimentally Created Disordered Occlusionmentioning
confidence: 99%
“…Two blinded examiners separately measured disc thickness for the anterior band, intermediate zone, and posterior band in 10 randomly selected sections per joint, with the averages pooled (N = 6/group). The longest linear distance was measured for the anterior and posterior bands, but the shortest distance was measured for the intermediate zone (Sun et al, 2009 …”
Section: Tissue Harvest and Measurement Of Disc Thicknessmentioning
confidence: 99%
“…It is also suggested that the position of the MF could be influenced by the function of the condyle or an influence of the mandible [12,16,22,23,30]. Also, the influence of the dental function is described as a possible modulator of the continuous alteration of the morphology of the TMJ [15,36,45]. Some differences in the position between different dentoskeletal frames and its influence as a possible etiological factor in the development of malocclusion have been previously reported by some authors using 2D analysis with linear measurements or using geometric morphometrics.…”
Section: Introductionmentioning
confidence: 99%